An Activity Theory Approach to surfacing the pedagogical object in a primary school mathematics classroom - Hardman, Joanne (Outlines. Critical Practice Studies, 2007)
This paper develops a methodology for using Activity Theory (AT) to investigate pedagogical practices in primary school mathematics classrooms by selecting object-oriented pedagogical activity as the unit of analysis. While an understanding of object-oriented activity is central to Activity Theory (AT), the notion of object is a frequently debated and often misunderstood one. The conceptual confusion surrounding the object arises both from difficulties related to translating the original Russian conceptualisation of object-oriented activity into English as well as from the different interpretations of the object currently in use within two contemporary approaches in activity theory. This paper seeks to clarify understandings of the object by exploring notions of object oriented activity. To this end, the paper traces the historical development of the object through Leontiev (1978; 1981) and Engeström’s (1987; 1999) expansion of Vygotsky’s original triadic understanding of object oriented activity. Drawing on Basil Bernstein’s (1996) notion of evaluative criteria as those rules that transmit the criteria for the production of a legitimate text, the paper goes on to elaborate a methodology for using AT to analyse observational data by developing the notion of “evaluative episodes” as pedagogical moments in which the pedagogical object is made visible. Findings indicate that an evaluative episode can serve as an analytical space in which the dynamism of an activity system is momentarily frozen, enabling one to model human activity in the system under investigation and, hence, in this study, to understand pedagogy in context.